2004
DOI: 10.1002/pssb.200405218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high pressure on the photoluminescence transitions of excitons in α‐PTCDA (perylene tetracarboxylic dianhydride) crystals

Abstract: PACS 62.50.+p, 78.55.Kz We report investigations of the photoluminescence (PL) spectrum of α-PTCDA single crystals at 11 K and 300 K as a function of applied pressures to 54 kbar carried out using a diamond-anvil cell with annealed methanol-ethanol medium. The effects of pressure are observed on several excitonic PL features principally associated with: an excimer transition for the 300 K spectra, or an indirect Frenkel exciton and charge transfer exciton transitions (between stacked molecules in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The latter transition becomes dominant at room temperature. These band assignments have been supported in recent straindependent PL studies on ␣-PTCDA single crystals 23 and on crystalline PTCDA films. 24 In this work, we extend our studies to PTCDA/ Alq 3 multilayers and to codeposited films using temperaturedependent PL spectroscopy, x-ray diffraction, and Fourier transform infrared ͑FTIR͒ spectroscopy.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The latter transition becomes dominant at room temperature. These band assignments have been supported in recent straindependent PL studies on ␣-PTCDA single crystals 23 and on crystalline PTCDA films. 24 In this work, we extend our studies to PTCDA/ Alq 3 multilayers and to codeposited films using temperaturedependent PL spectroscopy, x-ray diffraction, and Fourier transform infrared ͑FTIR͒ spectroscopy.…”
Section: Introductionsupporting
confidence: 58%
“…27 However, recent PL studies on PTCDA/ Alq 3 bilayers reveal 24 that the low-energy band only occurs if the PTCDA film is grown on Alq 3 while it disappears when Alq 3 is grown on PTCDA, demonstrating that the low-energy band is not generated by a PTCDA/ Alq 3 interface transition. Instead, pressure-dependent PL measurements on PTCDA crystals 23 and on crystalline PTCDA layers 24,28 show that the low-energy peak can be attributed to a strain-modified CT2 transition. Compressive strain along the orbitals of stacked molecules causes an enhancement of the CT2 exciton binding energy and an increased exciton formation probability explaining the redshifted and stronger pronounced CT2 emission in the PL spectrum.…”
Section: Methodsmentioning
confidence: 97%
“…In recent PL studies under pressure, it was found that all PL bands are shifted to lower energies, with a pressure coefficient of the order of −4 meV/ kbar to − 6 meV/ kbar, 85 in the same range as the pressure-induced shift of the lowenergy tail of linear absorption of −6 meV/ kbar observed earlier. 86 The dimer potential depicted in Fig.…”
Section: E Pressure Dependence Of Excimer Transitionsupporting
confidence: 51%
“…6, the minimum shifts towards smaller stack distances, resulting in a redshift of the excimer of −7.4 meV/ kbar, close to the observed pressure dependence. 85 This theoretical estimate is somewhat preliminary as the influence of pressure on the reduction of the b and c lattice vectors cannot be investigated with simple dimer models: Each molecule will be compressed internally, and changes of the molecular orientiation in the unit cell could modify the delicate balance between the intermolecular interactions.…”
Section: E Pressure Dependence Of Excimer Transitionmentioning
confidence: 99%
“…The applied strain has been estimated from PL experiments on sublimed PTCDA single crystals using a cryogenic diamondanvil cell. 49 As demonstrated in Fig. 9, the low-energy CT2 emission slightly shifts to lower energy and increases its intensity when uniaxial strain P 1 (about 0.5 kbar) and higher strain P 2 (about 1 kbar) is applied to the PTCDA film.…”
Section: B Ptcda/ Alq 3 Multilayersmentioning
confidence: 81%